Analysis and evaluation of germplasm difference of Xanthoceras sorbifolium Bunge in different producing areas in Shandong and Liaoning - LI Shengxin; ZHANG Ziyan; QI Hongtao; GUAN Wenbin; LI Shouke; SUN Jie (Xibei zhiwu xuebao)
[Objective] In order to examine the quality of Xanthoceras sorbifolium Bunge germplasm resources in different regions, it is necessary to establish appropriate evaluation methods for the selection of excellent germplasm resources. [Methods] 16 indicators, including water content, protein content, oil content, and fatty acid composition of seeds, were determined from 20 different varieties of X . sorbifolium Bunge in Liaoning and Shandong. Correlation analysis, principal component analysis, and cluster analysis were used to evaluate the quality of germplasm resources. [Results] The coefficient of variation of germplasm resources ranged from 6.43% to 49.11%, and the correlation analysis revealed significant relationships among the 16 indicators. 5 principal components were selected by principal component analysis, and the cumulative variance contribution rate was 82.951%. Transverse diameter, longitudinal diameter, hundred-grain weight, oil content, nervonic acid, and other 6 unsaturated fatty acid content were the key indicators to evaluate the germplasm resources of X . sorbifolium Bunge. The results of cluster analysis showed that the 20 X . sorbifolium Bunge germplasm resources could be categorized into three groups according to the quality indicators. [Conclusion] ‘SW-180’ has higher oil content and ‘JD-1’ has higher nervonic acid content, which can be selected for directional cultivation. Overall, ‘JW-1’, ‘JGZ-1’, ‘JD-1’, and ‘JGZ-5’ perform well based on their comprehensive scores, which can be used as excellent parent materials for breeding.